Bear - Engel, Marian (Toronto : McClelland & Stewart, 1990)
Lou is a lonely librarian who spends her days in the dusty archives of the Historical Institute. When an unusual field assignment comes her way, she jumps at the chance to travel to a remote island in northern Ontario, where she will spend the summer cataloguing a library that belonged to an eccentric 19th-century colonel. Eager to investigate the estate's curious history, she is shocked to discover that the island has one other inhabitant: a bear. Lou's imagination is soon overtaken by the island's past occupants, whose deep fascination with bears gradually becomes her own. Irresistibly, Lou is led along a path of emotional and sexual self-awakening, as she explores the limits of her own animal nature. What she discovers will change her life forever.
Keywords: Emotional maturity -- Fiction; Libraries -- Fiction